A Hierarchical Approach to Technology Roadmapping within an RTO Environment: A proposed new digital hierarchical technology roadmapping architecture can integrate and align research activities with the manufacturing capabilities needed by industry. Issue 3 (4th May 2021) - Osborne, Peter; Routley, Michèle; Ilevbare, Imoh
Abstract : Overview: Many organizations use technology roadmaps for strategic planning, and they often use workshop-based approaches to create the roadmaps. Customizing the workshop process and the artifacts used is necessary to tailor the approach to each organization's context. We describe a hierarchical architecture and software-supported workshop approach that we deployed within the UK's High Value Manufacturing Catapult. This customized approach connected technological capabilities identified within multiple organizations' technology roadmaps with different industry needs identified within sector roadmaps. This development process provided a framework to facilitate discussion between academia and industry and to build a clear set of narratives linking the development of new technologies with industry challenges. By digitizing the workshop outputs in a common database, we integrated multiple narratives dynamically, supported different views for the various stakeholders involved, and facilitated reuse of roadmapping elements generated in different workshops.